Modelling of Extreme Hydrological Events on a Tisza River Basin Pilot Area, Hungary - Vizi, Dávid Béla; Fehér, János; Lovas, Attila; Kovács, Sándor (Journal of Environmental Geography, 2018)
Climate change takes more and more challenges to the water management. Future predictions show that the possibility of extreme floods and drought events are increasing, thus an additional task of the water management can be the fulfilment of the increasing water demands. These new extreme hydrological situations need to be properly handled in water management. The paper presents the first modelling results of the JOINTISZA project carried out on a selected sub-basin of the Tisza River, which is endangered by hydrological extremes. Our aim was to demonstrate the applicability of a one-dimensional hydrodynamic model to study the effects of the climate change. Future hydrological trends were introduced in the river basin and it was assessed how the results of climate models can be used for further hydrodynamic modelling. To address challenges of climate change and supply the stakeholders with an adequate amount of water, proper operation of the reservoir and the irrigation canals are needed. The use of hydrological modelling can be helpful to adequately distribute water resources.